THE ASSESSMENT ON CLASSROOM MANAGEMENT SKILLS OF PRIMARY SCHOOL TEACHERS - Aslı YÜKSEL (Fırat University, 2019)
The aim of this study is to determine the level of classroom management skills of the primary school teachers according to the views of teachers, teacher candidates and observers. This research is a descriptive survey model study. The research population consists totally of 543 primary school teachers who work in 49 primary schools (2 of them are private and 47 of them are state schools) in the centre of Afyonkarahisar during the academic year of 2011-2012. Since it is possible to reach the whole population, sample was not taken. However, 200 primary school teacher candidates, studying their third and final year at Afyon Kocatepe University, Faculty of Education were included in the population of the study. Both quantitative and qualitative data collection techniques were employed during data collection. In the study, “Classroom Management Teacher Questionaire” and “Teacher Observation Form” were used as data collection tools.. The data obtained from this study were analyzed by using SPSS 15.0 for Windows. Arithmetic mean, standard deviation, frequency and percentage were used while analysing the data. Apart from that, Mann-Whitney U Test of non-parametric tests were used for the groups of two and for more than two groups Kruskal - Wallis H Test was used. Besides; Wilcoxon Signed Rank Test was used for the qualitative analysis of the data. According to the views of teachers and teacher candidates, in terms of the level of classroom management skills, it has been concluded that the sub-dimension that teachers have the highest average is Communication, but by the results of the observation that is Time Management sub-dimension. With respect to the views of teachers and teacher candidates and observers, the sub-dimension that teachers have the lowest average is Physical Layout of the Classroom. When classroom management skills were evaluated as a whole in terms of teachers and observation results, the level of classroom management skills of the primary school teachers is “Always”, but in terms of teacher candidates the level is “Sometimes”. It has been found that while the level of classroom management skills of primary school teachers display a significant difference according to gender, their seniority and grade level they teach; there is no significant difference according to their graduate school or classroom size.